The effects of childhood trauma and mental disorders on treatment engagement, contact with the criminal justice system, and mortality among people with opioid dependence. (1st February 2023) - Santo, Thomas; Gisev, Natasa; Campbell, Gabrielle; Nelson, Elliot; Degenhardt, Louisa
Abstract: Background: Childhood trauma and mental disorders increase the risk of opioid dependence. We aimed to examine whether childhood trauma and mental disorders are associated with opioid agonist treatment (OAT) engagement, contact with the criminal justice system, and mortality among people with opioid dependence. Methods: This observational study linked survey data from 1482 people receiving OAT in Sydney, Australia (2004–2008) to administrative data on OAT, crime, and mortality through 2017. We used survey data to assess childhood trauma, depression, panic disorder, post-traumatic stress disorder (PTSD), borderline personality disorder, anti-social personality disorder (ASPD), and comorbid substance dependence. We used discrete-time analysis to examine time from opioid dependence onset to OAT entry and mortality. Poisson regressions were used to analyze time receiving OAT and number of charges. Results: Participants with extensive childhood trauma histories and ASPD were less likely to enter OAT and those with depression were more likely to enter OAT in any given year after opioid dependence onset. Panic disorder, PTSD, and borderline personality disorder were associated with less time in OAT. Extensive histories of childhood trauma, PTSD, ASPD, and comorbid substance dependence increased risk of charges for any offence. There were no significant associations between the exposure variables and mortality. Conclusions: Our findings suggest that childhood trauma and mental disorders increase the risk of adverse treatment and social outcomes among people with opioid dependence. Interventions that aim to reduce harm among people with opioid dependence may consider the effect of childhood trauma and mental disorders on OAT engagement and crime. Highlights: Assessed childhood trauma & mental disorders among 1482 people in OAT from 2004 to 08. Childhood trauma & ASPD slowed transition from opioid dependence onset to OAT. Depression associated with faster transition to OAT. Panic disorder, PTSD, & borderline personality disorder linked to less time in OAT. Childhood trauma, PTSD, & ASPD increased contact with criminal justice system.